2021
DOI: 10.3390/ph14040372
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Benzimidazole-Based Anthelmintics and Their Enantiomers as Repurposed Drug Candidates in Cancer Therapy

Abstract: Repurposing of approved non-antitumor drugs represents a promising and affordable strategy that may help to increase the repertoire of effective anticancer drugs. Benzimidazole-based anthelmintics are antiparasitic drugs commonly employed both in human and veterinary medicine. Benzimidazole compounds are being considered for drug repurposing due to antitumor activities displayed by some members of the family. In this study, we explored the effects of a large series of benzimidazole-based anthelmintics (and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…From this point of view, antimicrobial peptides (AMPs) seem to be attractive and promising tools in medical sciences. Additionally, many metallo-complexes characterized in recent years have been applied in the treatment of anti-inflammatory infections, cancer, and neurodegenerative diseases [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, antimicrobial peptides (AMPs) seem to be attractive and promising tools in medical sciences. Additionally, many metallo-complexes characterized in recent years have been applied in the treatment of anti-inflammatory infections, cancer, and neurodegenerative diseases [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drug repurposing of benzimidazole compounds is generally considered for the reason that, it has antitumor activities. Florio and coworkers screened anthelmintics which are derivatives of benzimidazole [37]. Certain drugs like albendazole (3), flubendazole (9), oxibendazole (10) etc.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Benzimidazole-based anthelmintics are a family of drugs widely employed both in human and in veterinary medicine for the treatment of intestinal parasites [104]. Interestingly, there is a growing number of studies reporting that several members of this family display both in vitro and in vivo antitumor effects in multiple tumor models, including PC [29,[105][106][107]. In particular, Florio et al showed that parbendazole (Figure 1), at dosages in the range of the therapeutic plasma concentrations, inhibits growth and abolishes clonogenicity of PC cells by fostering apoptosis, drastic cell cycle perturbation and DNA damage response [29].…”
Section: Benzimidazole-based Anthelminthicsmentioning
confidence: 99%
“…Notably, the combined treatment of parbendazole with the PC standard chemotherapeutic drug gemcitabine synergistically affects PC cell viability, supporting the relevance of parbendazole in the perspective of clinical translation. Intriguingly, considering that pharmaceutically active compounds may modulate multiple molecular targets with a plethora of mechanisms of action, putative polypharmacological profiles of a wider series of benzimidazoles were explored by using an in silico target prediction approach [106]. Notably, for the two derivatives fenbendazole and mebendazole, the bioinformatic tool highlighted a few previously underexplored cancer-related targets having very high probability scores, namely MAP kinase p38 alpha, vascular endothelial growth factor receptor 2 (VEGFR2) and the tyrosine-protein kinase ABL [106].…”
Section: Benzimidazole-based Anthelminthicsmentioning
confidence: 99%
See 1 more Smart Citation